The STRETCHING HAMSTRING EXERCISE DAN STRENGTHENING QUADRICEP MUSCLE EXERCISE TERHADAP PENINGKATAN AKTIVITAS FUNGSIONAL PENDERITA OSTEOARTHTRITIS GENU: STRETCHING HAMSTRING EXERCISE DAN STRENGTHENING QUADRICEP MUSCLE EXERCISE TERHADAP PENINGKATAN AKTIVITAS FUNGSIONAL PENDERITA OSTEOARTHTRITIS GENU - Dwi Yuliyani, Anisa (STIKES Telogorejo Semarang, 2023)
In the population of developing countries, moderate or severe disability due to osteoarthritis is 10 percent, while in the population of low-income countries it reaches 33.5%, and disability due to arthrosis occupies 43.4% of the world's population. Osteoarthritis affects about 21% of adults (46.4 million people) in the United States, and this number is expected to increase to 67 million by 2030. Hamstring stretching exercises are very effective at increasing the flexibility of muscles and joints, thereby reducing or eliminating joint pain. This exercise can also improve circulation and strengthen bones. Strengthening the quadriceps muscles helps reduce pain, improves body function and quality of life for patients and slows disease progression. WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) is an index used to assess the condition of patients with osteoarthritis of the knee. Questions consisted of pain, stiffness, physical and social functioning. This study used a pre-experimental method with a pre-test and post-test research design that aimed to determine the effect of giving stretching hamstring exercise and strengthening quadriceps muscle exercise. The conclusion is that there is an effect of stretching hamstring exercise and strengthening quadriceps muscle exercise on increasing the functional activity of patients with osteoarthritis genu